Digital strategies for reshaping the competitiveness of HOPSCA - HOI, Wafong (Institutional Knowledge at Singapore Management University, 2021)
The digital transformation strategy has a profound impact on the commercial real estate industry in China. However, so far, research on digital innovation strategies in the business field predominantly surrounds the retailing and systematic research identifying the effect of digital strategies on HOPSCA and commercial operational service provider has yet to be conducted. On the issue of digital transformation strategies of HOPSCA, there is currently a lack of relevant empirical evidence in the fields of management and economics to quantitatively analyze its effects, and there is not readily available and reliable experience for reference in the business practices. Based on real-world business scenarios deployed by digital tools jointly developed by IT Corporation Y, Property Corporation B, and Tencent Holdings Ltd., this dissertation regards specific HOPSCA (shopping malls) as the analysis unit and takes advantages of unique first-hand business data and statistical causal identification methods, striving to make up for this research gap. This dissertation highlights three dimensions of the HOPSCA digital strategies, namely Digitalization, Networkization, and Intelligentized. Based on the technical attributes of different digital tools, it proposes a taxonomy of technologies under the above-mentioned three dimensions and the conceptual framework of “Accuracy-Prediction-Quality-Linkage”(准-预-质-连).Based on business practice, literature summary and theory, this dissertation puts forward a set of hypotheses that can be tested quantitatively and empirically. By combining the first-hand business data with the Difference-in-Differences method, we examine the effect of digital tools on the competitiveness of HOPSCA. The result suggests that the deployment of PMS/AMP can effectively reduce the cost of labor and management, improve operation efficiency, and increase NOI. When the scale of assets under management gets larger, the marginal benefits become more significant. The Precise Customer- flow Statistics System can greatly improve the accuracy and reliability of customer-flow statistics data, distinguish customer segments, and provide direct and powerful customer preference data for targeted marketing and leasing strategies. When it is connected to the Membership management system, it can make marketing more efficient and increase the input-output ratio for marketing and operation. The interrelation and combination of various digital tools can produce synergistic and interactive effects. On the mechanism, digital tools have multiple channels that sharpen the competitiveness of HOPSCA. First, digital tools can increase the customer-flow, the total number of members, and the number of stores that customers visit. By improving these direct factors, digital tools will then have an impact on the performance of HOPSCA. Secondly, digital tools can have an impact on consumer behavior preferences, thereby improving the fitness between consumer preferences and HOPSCA’s tenant and brand mix, thereby enhancing the competitiveness of HOPSCA. Finally, digital tools can also affect the competitiveness of HOPSCA by changing the strategies and practices of HOPSCA operations (for example, digital tools can improve the efficiency of operation management, optimize business format portfolio or traffic flow settings through digital transformation). Based on the above conclusions, we have put forward a few of feasible industry recommendations, the significance of which lies in guiding the application of digital technologies in HOPSCA, laying the foundation for studying how digital technologies can create effective added value for business, and providing a theoretical basis for Chinese commercial real estate operators’ new digital strategies. These recommendations also focus on bringing about industry technology innovation and introduce feasible technology roadmaps to other HOPSCA in China and the world.